2016
DOI: 10.1063/1.4963796
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation and control of the interfacial polarization in organic light-emitting diodes by dipolar doping

Abstract: Most of the commonly used electron transporting materials in organic light-emitting diodes exhibit interfacial polarization resulting from partially aligned permanent dipole moments of the molecules. This property modifies the internal electric field distribution of the device and therefore enables an earlier flat band condition for the hole transporting side, leading to improved charge carrier injection. Recently, this phenomenon was studied with regard to different materials and degradation effects, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 33 publications
9
69
0
Order By: Relevance
“…Furthermore, the driving forces of molecular orientation remain uncertain in terms of solid-state physics, leading to several researches focusing on OLED materials 44,45,50-53 . Additionally, various experiments and simulations have been conducted over the previous decade with an objective of understanding the molecular orientation of SAE materials, which are also known to form amorphous films 28,29,32,42,54,55 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the driving forces of molecular orientation remain uncertain in terms of solid-state physics, leading to several researches focusing on OLED materials 44,45,50-53 . Additionally, various experiments and simulations have been conducted over the previous decade with an objective of understanding the molecular orientation of SAE materials, which are also known to form amorphous films 28,29,32,42,54,55 .…”
Section: Resultsmentioning
confidence: 99%
“…The observed values are more suitable for thermally stable device applications and which enhance the morphological properties during device fabrication. Consequently, our materials revealed a higher melting point of 351 • C. TPA-1A showed outstanding thermal properties than well-known reference hole-transporting materials NPB (98 • C) and TPD (65 • C) due to its highly conjugated structure and rigid diphenyl acridine moiety attached to the triphenylamine central core [38,39]. …”
Section: Thermal and Morphological Propertiesmentioning
confidence: 85%
“…Consequently, our materials revealed a higher melting point of 351 °C. TPA-1A showed outstanding thermal properties than wellknown reference hole-transporting materials NPB (98 °C) and TPD (65 °C) due to its highly conjugated structure and rigid diphenyl acridine moiety attached to the triphenylamine central core [38,39]. The morphological studies of films are supported by scanning electron microscope (SEM) imagery and depicted in Figure 2.…”
Section: Thermal and Morphological Propertiesmentioning
confidence: 89%
“…J€ ager et al have shown that by mixing Alq 3 into an a-NPD matrix the polarity of the HTL can be controlled. 56 The electron transport material Al(7-Prq) 3 has been demonstrated by Noguchi et al to exhibit an inverted polarization with a sheet charge density of þ3.1 mC/m 2 . 57 In a bilayer configuration as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In Alq 3 , the polar sheet density has been reported by several groups to lie around À1.1 mC/m 2 -with the negative polarity at the HTL/ETL interface-confirmed by displacement current measurement, 58,59 capacitance-voltage, 34 and ). 56 Obviously, the fabrication conditions play a role in the formation of the macroscopic polarization. Other polar electron transport materials exhibiting orientation polarization are TPBi (À1.1 mC/m .…”
Section: Discussionmentioning
confidence: 99%